Question Simplify the expression x2+2x+1 Evaluate (−x−1)2A negative base raised to an even power equals a positive (x+1)2Use (a+b)2=a2+2ab+b2 to expand the expression x2+2x×1+12Solution x2+2x+1 Show Solution Find the roots x=−1 Evaluate (−x−1)2To find the roots of the expression,set the expression equal to 0 (−x−1)2=0The only way a power can be 0 is when the base equals 0 −x−1=0Move the constant to the right-hand side and change its sign −x=0+1Removing 0 doesn't change the value,so remove it from the expression −x=1Solution x=−1 Show Solution